1996
DOI: 10.1183/09031936.96.09020346
|View full text |Cite
|
Sign up to set email alerts
|

Human alveolar capillaries undergo angiogenesis in pulmonary veno-occlusive disease

Abstract: H Hu um ma an n a al lv ve eo ol la ar r c ca ap pi il ll la ar ri ie es s u un nd de er rg go o a an ng gi io og ge en ne es si is s i in n p pu ul lm mo on na ar ry y v ve en no o--o oc cc cl lu us si iv ve e d di is se ea as se e ABSTRACT: The bronchial circulation undergoes angiogenesis in several pathological conditions, such as lung neoplasm and bronchiectasis, but whether the pulmonary circulation can do this has been questioned. A woman treated with mitomycin C and 5-fluorouracil developed progressive,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…These abnormalities may be explained by interstitial oedema and/or pulmonary capillary angiogenesis secondary to chronic pulmonary venous obstruction [37]. Interstitial lung disease may indeed be identified in PVOD [12].…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities may be explained by interstitial oedema and/or pulmonary capillary angiogenesis secondary to chronic pulmonary venous obstruction [37]. Interstitial lung disease may indeed be identified in PVOD [12].…”
Section: Discussionmentioning
confidence: 99%
“…Extensive capillary damage and venous occlusion were observed, resulting in excessive new capillary formation, sometimes in angiomatoid configurations, and hypertrophy of pulmonary veins and arteries. 33 At the molecular level, it has been suggested that MMCinduced pulmonary vascular dysfunction may be related to its bifunctional alkylating property. Cultured pulmonary-artery endothelial cells exposed to MMC showed similar growth arrest and morphological alterations to monocrotaline pyrrole, another bifunctional alkylating substance known to be a potent trigger for experimental PH in rats.…”
Section: Discussionmentioning
confidence: 99%
“…24 Schraufnagel has also suggested there is new vessel formation in the lungs of a patient with pulmonary venoocclusive disease. 25 At least some metastatic tumors in the lung receive their blood supply either exclusively or predominately from the pulmonary circulation, again suggesting the ability of the pulmonary circulation to undergo an angiogenic response. 26 In further support of the idea that pulmonary angiogenesis may occur in response to chronic hypoxia is the recent report from Pascaud et al, who found that angiostatin, an inhibitor of angiogenesis, aggravated pulmonary hypertension in the hypoxic lung.…”
mentioning
confidence: 99%